Europas Gedächtnis : Das neue Europa zwischen nationalen Erinnerungen und gemeinsamer Identität - König, Helmut; Schmidt, Julia; Sicking, Manfred (Europäische Horizonte, 2008)
The founding treaties of the European Community were signed on March 25, 1957 in Rome by France, the Federal Republic of Germany, Italy, Belgium, the Netherlands and Luxembourg. In the meantime, the Europe of the six has become an amalgamation of now 27 states. Guided by the vision of European unification, according to which war in Europe can only be prevented by peaceful unification of peoples, the European Union has developed in a long process of integration and deepening. Five decades after the establishment of the institutionally constituted common Europe, the question must be discussed whether the community also has a people-borne identity. An elementary component of every identity is the awareness of a shared memory. Does this even exist in Europe? What is remembered? Half a century since the Treaty of Rome? Or is there a deeper historical memory of Europeans beyond the respective national memory? With contributions by Etienne François, Norbert Frei, Bronislaw Geremek, Anthony Giddens, Helmut König, Adolf Muschg, Karl Schlögel and Hans-Ulrich Wehler.